EKSPERIMENTASI MODEL PEMBELAJARAN TEAMS ASSISTED INDIVIDUALIZATION DITINJAU DARI ADVERSITY QUOTIENT SISWA - Wijayanti, Septiana; Yuliana, . (JURNAL e-DuMath, 2016)
This research aimed to find out: (1) which one gives better in mathematics learning achievement, learning models of Teams Assisted Individualization or conventional, (2) which one have better in mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient, (3) in each learning model, the level of Adversity Quotient which one have better mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient, (4) in each studentâs level of Adversity Quotient which one gives better in mathematics learning achievement, learning models of TAI or conventional. This research was a quasi-experimental research with 2 x 3 factorial design. The population of research was all students in XI IPA SMA Negeri 1 Pulokulon. The samples were chosen by using cluster random sampling. The instruments that were used to collect the data were the documentation of mathematics achievement, questionnaire of Adversity Quotient and test of mathematics achievement. The result of research showed as follows: (1) learning model TAI provided better learning achievement than conventional, (2) the students having climbers, campers, and quitters had equally mathematics learning achievement, (3) in each learning model, the students having climbers, campers, and quitters had equally mathematics learning achievement, (4) in each Adversity Quotient, learning model TAI provided better learning achievement than conventional. Keywords: teams assisted individualization, adversity quotient